The Effect of Good Corporate Governance and Board Gender Diversity on Firm Value with Earnings Management as a Moderating Variable - Sukma Wati, Ni Made Erika; Sri Werastuti, Desak Nyoman; Sinarwati, Ni Kadek (Dinasti Publisher, 2026)
This study examines the influence of Good Corporate Governance (GCG) and Boards Gender Diversity on firm value, with earnings management serving as a moderating variable. Inconsistent findings in prior research have prompted a deeper investigation into how governance quality and gender diversity shape firm value across various industries. A quantitative approach was employed using secondary data obtained from financial and annual reports of companies in the Energy, Financials, Healthcare, and Technology sectors listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample consisted of 101 companies, resulting in 303 firm-year observations. Data were analyzed using Moderated Regression Analysis (MRA) with Stata17 software. The results indicate that both GCG and Boards Gender Diversity have a positive and significant impact on firm value. Furthermore, earnings management strengthens the relationship between GCG and firm value but does not moderate the relationship between Boards Gender Diversity and firm value. These findings highlight that sound governance practices can enhance investor confidence and improve firm valuation. In contrast, gender diversity on corporate boards, while valuable for inclusivity and decision-making perspectives, does not significantly influence firm value when earnings management practices are present.